Decision Making in Acquisitions: The Effect of Outside Directors’ Compensation on Acquisition Patterns - Deutsch, Yuval; Keil, Thomas; Laamanen, Tomi (Journal of Management, 2007)
This article examines how the compensation paid for outside directors affects firms’ acquisition behavior. Using panel data of Standard & Poor’s 1500 firms between 1996 and 2002, the authors find that stock and stock option pay for outside directors are related in an inverted U-shaped manner to a firm’s acquisition rate and that for stock options, this relationship is moderated by board composition. Their findings suggest a dual agency model of corporate governance, according to which not only executives’ incentives but also outside directors’ incentives should be aligned with the shareholder value creation.